Dimensi Kualitas Pelayanan, Kepuasan dan Kepatuhan Pajak - Nita Anggraheny Savitri; Theresia Woro Damayanti (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2018)
This study is conducted to identify the effect of service quality dimensions given by tax officials to the satisfaction and compliance of individual taxpayers. Service quality dimensions are measured by five points, tangibles, reliability, responsiveness, assurance and empathy of respondents. Data obtained in the form of primary data from 125 questionnaires using Convenience Sampling method. Research data then tested by using Partial Least Square. This research shows that the dimension of service quality consists of tangibles, reliability, responsiveness, assurance, and empathy have no significant effect to taxpayer compliance through service satisfaction, but service quality dimension have a direct and significant effect on taxpayer compliance. This means that personal taxpayer compliance is influenced by the quality of service.